SDSS-IV MaNGA – the spatially resolved transition from star formation to quiescence. Issue 3 (10th December 2016) - Belfiore, Francesco; Maiolino, Roberto; Maraston, Claudia; Emsellem, Eric; Bershady, Matthew A.; Masters, Karen L.; Bizyaev, Dmitry; Boquien, Médéric; Brownstein, Joel R.; Bundy, Kevin; Diamond-Stanic, Aleksandar M.; Drory, Niv; et al.
Abstract: Using spatially resolved spectroscopy from SDSS-IV MaNGA we have demonstrated that low ionization emission-line regions (LIERs) in local galaxies result from photoionization by hot evolved stars, not active galactic nuclei, hence tracing galactic region hosting old stellar population where, despite the presence of ionized gas, star formation is no longer occurring. LIERs are ubiquitous in both quiescent galaxies and in the central regions of galaxies where star formation takes place at larger radii. We refer to these two classes of galaxies as extended LIER (eLIER) and central LIER (cLIER) galaxies, respectively. cLIERs are late-type galaxies primarily spread across the green valley, in the transition region between the star formation main sequence and quiescent galaxies. These galaxies display regular disc rotation in both stars and gas, although featuring a higher central stellar velocity dispersion than star-forming galaxies of the same mass. cLIERs are consistent with being slowly quenched inside-out; the transformation is associated with massive bulges, pointing towards the importance of bulge growth via secular evolution. eLIERs are morphologically early types and are indistinguishable from passive galaxies devoid of line emission in terms of their stellar populations, morphology and central stellar velocity dispersion. Ionized gas in eLIERs shows both disturbed and disc-like kinematics. When a large-scale flow/rotation is observed in the gas, it is often misaligned relative to the stellar component. These features indicate that eLIERs are passive galaxies harbouring a residual cold gas component, acquired mostly via external accretion. Importantly, quiescent galaxies devoid of line emission reside in denser environments and have significantly higher satellite fraction than eLIERs. Environmental effects thus represent the likely cause for the existence of line-less galaxies on the red sequence.